2019
DOI: 10.1186/s12969-019-0305-x
|View full text |Cite
|
Sign up to set email alerts
|

The effects of TNF-alpha inhibitor therapy on the incidence of infection in JIA children: a meta-analysis

Abstract: BackgroundJuvenile Idiopathic arthritis (JIA) is the most common chronic rheumatic disease in childhood. The diagnosis is based on the underlying symptoms of arthritis with an exclusion of other diseases Biologic agents are increasingly used on the side of disease-modifying anti-rheumatic drugs (DMARD) in JIA treatment.Main bodyThe aim of this meta-analysis was to investigate the observed infections in JIA children during tumor necrosis factor (TNF)-alpha inhibitor therapy. A systematic search of three databas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(18 citation statements)
references
References 49 publications
2
16
0
Order By: Relevance
“…A lymphopenia less than 600/mL, but even less than 250 CD4 LT/mL and treatment with glucocorticoids in doses of more than 10 mg of prednisolone or its equivalent per day are more frequently associated with infections. 10,22 The lower lymphocyte count with a correlation of significance close to 5% and the response of specific antibodies to serotype 4 among non-responders in our study make it necessary to directly corroborate and/or assess response to pneumococcal vaccine in lymphopenic patients or those with low lymphocyte count below the cut-off point.…”
Section: Resultsmentioning
confidence: 75%
See 2 more Smart Citations
“…A lymphopenia less than 600/mL, but even less than 250 CD4 LT/mL and treatment with glucocorticoids in doses of more than 10 mg of prednisolone or its equivalent per day are more frequently associated with infections. 10,22 The lower lymphocyte count with a correlation of significance close to 5% and the response of specific antibodies to serotype 4 among non-responders in our study make it necessary to directly corroborate and/or assess response to pneumococcal vaccine in lymphopenic patients or those with low lymphocyte count below the cut-off point.…”
Section: Resultsmentioning
confidence: 75%
“…In parallel, the increased risk of infections associated with the use of glucocorticoids has been demonstrated widely, especially in lymphopenic patients, but there are no data regarding its role in response to pneumococcal vaccines. 10,12 Patients receiving chronic immunosuppressive therapy with glucocorticoids and/or DMARDs can develop severe lymphopenia, involving all types of lymphocytes. A lymphopenia less than 600/mL, but even less than 250 CD4 LT/mL and treatment with glucocorticoids in doses of more than 10 mg of prednisolone or its equivalent per day are more frequently associated with infections.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The study reported that the majority of infections were located in the upper respiratory tract. Yet, significant increase in the infection rate could not be detected ( 27 ). Beukelman et al reported that steroid-sparing DMARD therapies may reduce the risk of severe infections in children since high-dose steroid therapy may increase the infection rate 3-fold in JIA patients ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 99%
“…To date, our results demonstrated for the first time that CD56 NK-cells were significantly decreased in the MTX/ADA group compared to healthy controls. It might be an explanation of the increased number of mild, viral, upper respiratory tract infections demonstrated in various trials ( 27 ). Other parts of the innate immune-system like complements and phagocyte levels did not show any alteration.…”
Section: Discussionmentioning
confidence: 99%